DETERMINANTS OF ENVIRONMENTAL QUALITY IN SUMATRA ISLAND: A SPATIAL ECONOMETRIC APPROACH - Osi Hayuni Putri; Silvia Rahayu; Masrida Zasriati; Mira Hastin (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
Environmental quality is an essential indicator for supporting sustainable development. As a region characterized by intensive economic activities, Sumatra Island faces various environmental challenges arising from economic growth, population expansion, energy consumption, transportation activities, and investment flows. This study aims to examine the effects of Gross Regional Domestic Product (GRDP), population, energy consumption, the number of motor vehicles, the Human Development Index (HDI), and Foreign Direct Investment (FDI) on environmental quality in Sumatra Island while considering spatial interactions among regions. The study employs panel data from ten provinces in Sumatra during the period 2019–2023. The analysis was conducted using the Spatial Error Model with Random Effects (SEM-RE) after performing Moran’s I spatial autocorrelation test and selecting the most appropriate spatial model. The results indicate that GRDP has a negative and significant effect on environmental quality. In contrast, HDI and FDI have positive and significant effects on environmental quality. Meanwhile, population, energy consumption, and the number of motor vehicles do not significantly affect environmental quality. The spatial parameter value of 0.545 indicates the presence of significant spatial dependence among regions. These findings suggest that environmental quality in a province is influenced not only by internal factors but also by environmental conditions in neighboring regions. Therefore, regionally integrated environmental policies are required to improve environmental quality across Sumatra Island.